Effectiveness of Combination Acupressure Therapy and Murotal Al-Qur'an to Reduce Blood Pressure of the Elderly - Riska Oktalina; Syamsul Anwar; Siti Badriah (Jurnal Penelitian Pendidikan IPA, 2024)
Hypertension is blood pressure that increases beyond normal limits. In the elderly, the type of hypertension that is often encountered is isolated systolic hypertension (ISH), which is high systolic pressure above 140 mmHg, but diastolic pressure remains at average numbers below 90 mmHg. One of the complementary therapies that can be used by the elderly who have hypertension is acupressure and murottal therapy of the Quran. This study aims to determine the effectiveness of acupressure and murotal combination therapy of the Qur'an on blood pressure in elderly people with hypertension. The research design used was quasi-experimental with two group pretest and posttest design with a control group. The population in this studi were elderly with hypertension. The sampling technique used total sampling, namely 36 hypertensive elderly and divided into 18 intervention groups and 18 control groups. During 6 days, they are given intervension combination acupressure and murotal combination therapy of the qur'an. The analysis of this study used univariate, bivariate analysis with paired sample T-Test and independent T-Test, and multivariate analysis with GLM. Data processing in this study used SPSS version 26.0. The findings showed that the systolic and diastolic, in elderly people with hypertension decreased after being given combined therapy with acupressure and murottal therapy of the Quran therapy (p value = 0.000). doing a combination of acupressure and murotal treatment of the Qur'an can provide a mental calm effect on the elderly and improve blood flow, to reduce blood pressure in the elderly who have hypertension. It is hoped that this research can be a reference and can be used as one of the non-pharmacological therapeutic interventions using acupressure and murotal combination therapy of the Qur'an in providing nursing care, especially for the elderly who have hypertension.